PENGARUH INTERNET TERHADAP PENURUNAN MINAT BELAJAR MAHASISWA - Miskahuddin Miskahuddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
The Internet is one result of the sophistication and advancement of science and man-made technology. Various conveniences offered, one of which is social media. But unfortunately, this sophistication has an impact on the quality of education. The worst impact in the world of education that may result from social networking sites is beginning to decrease interest in student learning. This is probably because the student's learning motivation also becomes reduced because of the importance of social networking rather than the learning achievement. To minimize the negative impact, as users we must be more intelligent. Internet savvy is how an internet user can manage and utilize internet technology wisely tailored to the needs and not violate ethical and internet codes of ethics.